Acoustic characteristics of post-traumatic scars of the eyelid tissues - I. A. Filatova; T. N. Kiseleva; K. V. Lugovkina; N. V. Guseva; Yu. A. Pavlenko (Российский офтальмологический журнал, 2022)
Purpose: to determine the acoustic characteristics ofvarious types o f tissue scarringfor the differentiation o f post-traumatic eyelid scars.   Materials and methods. 67 patients aged 32 to 67 (mean age 47.2 ± 9.5) with post-traumatic eyelid scarring were examined by ultrasoundgray-scale B-scan of tissues in the SmallPart mode and echodensitometry (Voluson Е 8 GE). The duration of the post-traumatic period of all patients was more than 12 months.   Results. Objective echographic criteria for quantitative assessing the formed scar tissue of the eyelids were developed, which helped determine the acoustic criteria for various types o f post-traumatic scars (normotrophic, atrophic, hypertrophic and keloid) and to supplement the existing clinical classification with echographic data.   Conclusion. Comprehensive ultrasound examination, which includes, tissue echodensitometry, along with B-scanning, is a highly informative method for the differential diagnosis ofvarious types of tissue scarring after eyelid injury.